2021
DOI: 10.3390/healthcare9040395
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses after Heavy Alcohol Consumption: Cytokine Concentrations in Hangover-Sensitive and Hangover-Resistant Drinkers

Abstract: This study investigated immunological changes during an alcohol hangover, and the possible difference between hangover-resistant and hangover-sensitive drinkers in terms of immune reactivity. Using a semi-naturalistic design, N = 36 healthy social drinkers (18 to 30 years old) provided saliva samples on a control day (after drinking no alcohol) and on a post-alcohol day. Hangover severity was rated directly after saliva collection. Cytokine concentrations, interleukin (IL)-1β, IL-6, IL-8, IL-10 and tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…These mean differences for anxiety and stress were however lower than the minimum change in scores found for individuals within the normative population to indicate improvement after receiving intervention (e.g., 3.9 for anxiety and 4.9 for stress) [24]. Additionally, the mean DASS-21 subscale scores for both hangover-sensitive and hangover-resistant drinkers were lower than the cut-off scores for the severity ratings [23], indicating mild levels of depression (10), anxiety (8), and stress (15). Finally, in the main analysis, the effect sizes for the mean differences between the two hangover groups for anxiety and stress were inconsequential (r = 0.05 and 0.03, respectively).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These mean differences for anxiety and stress were however lower than the minimum change in scores found for individuals within the normative population to indicate improvement after receiving intervention (e.g., 3.9 for anxiety and 4.9 for stress) [24]. Additionally, the mean DASS-21 subscale scores for both hangover-sensitive and hangover-resistant drinkers were lower than the cut-off scores for the severity ratings [23], indicating mild levels of depression (10), anxiety (8), and stress (15). Finally, in the main analysis, the effect sizes for the mean differences between the two hangover groups for anxiety and stress were inconsequential (r = 0.05 and 0.03, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…Individual differences in susceptibility to alcohol hangovers are not fully understood. Researchers have shown that the presence and severity of hangovers are related to an immune response to alcohol, in which the inflammatory effects of alcohol persist and manifest as hangover symptoms the following day [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to alcohol metabolism, other analyses focused on the inflammatory response caused by alcohol. Saliva samples from the participants of the study of Hogewoning et al [ 16 ] were analyzed to assess the concentration of a variety of cytokines [ 55 ]. Compared to the control day, on the alcohol day significant increases in saliva interleukin (IL)-6 and IL-10 concentrations were found in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences were found between the groups. Moreover, changes in cytokine concentration (alcohol day–control day) did not significantly correlate with hangover severity [ 55 ]. These observations were unexpected, as previous survey research suggested that the perceived immune fitness of hangover-resistant drinkers was significantly better that that reported by hangover-sensitive drinkers [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol can harm immune cells due to the formation of free radicals during metabolism, but antioxidants should provide protection against this [ 36 ]. Interestingly, the degree of a hangover the day after alcohol consumption does not affect alcohol-induced immune changes [ 37 ].…”
Section: The Impacts Of Alcohol Consumption On the Immune Systemmentioning
confidence: 99%